Drug Formulation Design - Shukla, Rahul; Kuznetsov, Aleksey; Ali, Akbar (IntechOpen, 2023)
This book discusses the theoretical and practical aspects required to formulate conventional drug dosage forms and advanced technology-based therapeutics. It is organized into four sections: "Preformulation", "Formulation Design and Approaches", "Characterization and Analysis", and "Cocrystal Engineering". The approaches discussed enhance the overall quality of treatment and overcome the side effects of available therapies. The book is a collection of scholarly literature relevant to pharmaceutical technology and existing pharmaceutical technologies. It is a useful reference for industrial personnel working on developing novel pharmaceutical dosage forms.